A Retrospective Review of Ileal Perforation in Children – 5 Years Audit from Tertiary Care Centre. - Noonavath, Ravindernaik; verma, Anju; K Ratan, Simmi (Journal of Neonatal Surgery, 2026)
Background: Peritonitis is one of the commonest causes for emergency surgeries conducted in surgical practice for a case of acute abdomen. Significance lies in association with high mortality and morbidity if not diagnosed and treated in time. Its frequency is more in developing countries, where medical facilities may not be readily available. The choice of procedure for source control depends on the patient’s condition as well as the surgeon preference. Material and Methods: A retrospective study was conducted and data collected for period of 5 years from June 2015 to May 2019 of children up to 12 years. A total of 56 patients presented in this period with ileal perforation. After resuscitation all patients underwent exploratory laparotomy and operative findings including site and number of perforations, status of peritoneal cavity noted. Managed with Primary repair or diversion stoma or resection & anastomosis as per intraoperative finding. Histopathological report was reviewed following surgery in all cases. Result: A total of 56 patients with Ileal perforation were included in the study of which 29 were males and 27 were females accounting for 51.7 percent and 48.2 percent respectively. Pain abdomen, vomiting and fever were the most common presenting complaints. Simple closure of the perforation and diverting ileostomy were the mainstay of the surgical management. Histopathological examination was nonspecific in 78.57% cases followed by tubercular (14.28%) and enteric fever (7.14%). Conclusion:Patients with ileal perforations are routinely seen in surgical emergencies and their demography, clinical profile, and intraoperative findings may guide the choice of procedure to be performed. The common pathology of Ileal perforation is Typhoid or Enteric fever, Non-specific ulcer, Tuberculosis and others. Nonspecific inflammation was the predominant cause in our study with operative findings similar to that of typhoid fever but no laboratory evidence of the disease was found.